Information System Design Activities Of Kuliah Kerja Nyata Using Single Linkage Method - -, Sugiarto; Putra, Chrystia Aji (Prosiding International conference on Information Technology and Business (ICITB), 2017)
The registration system of Kuliah Kerja Nyata (KKN) conducted at UPN "Veteran" East Java, is still manual, and takes time to queue at the KKN payment counter. This in the wake of the system of community service information that includes this KKN in order to facilitate students in the process and for the university can more easily in the formation of groups automatically.Peranan Group automatic grouping is very important for model random design group on later KKN. In this study the authors use the Single Linkage method. Single Linkage Method is a clustering hierarchical grouping method. Single Linkage method of grouping the data at the closest distance between groups, on some variables that exist in the Single Linkage is from the needs of LPPM UPN Veteran East Java, so officers in LPPM UPN Veteran East Java is no longer difficult in doing the division of students in each group of KKN.Â Keywords : Information System, Kuliah Kerja Nyata, and Single Linkage.